ANALISIS PROFIL RESORT CAGAR ALAM DOLOK SIBUAL-BUALI SEBAGAI PENENTU STRATEGI PENGELOLAAN KAWASAN - Wienda Lestari Br. Gurusinga; Siti Latifah; Siti Noor Chasanatun (Jurnal Agrotek Lestari, 2018)
Dolok Sibual Buali Nature Reserve with area’s large + 5000 hectares is one of the five resort models resort based management scope Hall of the North Sumatera’s Natural Resources Conservation. Before implement resort based management, must be known the resort profile. This research aims to known the resort profile of Dolok Sibual Buali Nature Reserve based the cover of vegetation and disturbance area by human activity. This research was conducted in the Nature Reserve Dolok Sibual Buali South Tapanuli on May-June 2013. The methods of data collection are observation and interviews. The data analysis consist of maps analysis and interview results analysis. The cover of vegetation in Dolok Sibual Buali Nature Reserve included safe category  with the secondary forest area’s large 4624.84 hectares or about 92.26 % of the total area. The other cover of vegetation are mixed farms, dry land farms, shrubs and rice fields. The form of disturbance area that comes from villages around the area are illegal logging, land conversion, wildlife hunting, theft of non-timber forest products and ecotourism. The conflicts that often occur between communities and area manager are conflicts about area boundaries. Communities also felt anxious caused the wildlife damaged their gardens. The management strategies that should be done are improved the area security and optimization the function of biodiversity preservation by apply the resort based management. Keywords: Cover of vegetation, disturbance area, Dolok Sibual Buali nature reserve, resort based management, resort profile